Hypoxia-induced compression in the tracheal system of the tobacco hornworm caterpillar, Manduca sexta - Greenlee, Kendra J. (Company of Biologists, 2013)
Abdominal pumping in caterpillars has only been documented during molting. Using synchrotron X-ray imaging in conjunction with high-speed flow-through respirometry, we show that Manduca sexta caterpillars cyclically contract their bodies in response to hypoxia, resulting in significant compressions of the tracheal system. Compression of tracheae induced by abdominal pumping drives external gas exchange, as evidenced by the high correlation between CO(2) emission peaks and body movements. During abdominal pumping, both the compression frequency and fractional change in diameter of tracheae increased with body mass. However, abdominal pumping and tracheal compression were only observed in larger, older caterpillars (>0.2 g body mass), suggesting that this hypoxic response increases during ontogeny. The diameters of major tracheae in the thorax increased isometrically with body mass. However, tracheae in the head did not scale with mass, suggesting that there is a large safety margin for oxygen delivery in the head in the youngest animals. Together, these results highlight the need for more studies of tracheal system scaling and suggest that patterns of tracheal investment vary regionally in the body.